Modularity in making: simplifying solution space for user innovation - Naik, Hari Suman; Fritzsche, Albrecht; Möslein, Kathrin (R & D Management, 2020)
An increasingly popular form of open innovation in the digital age is ‘making,’ where users innovate across multiple disciplines and make products that meet their needs, using mechanical, electronic, and digital components. These users have at their disposal, a wide solution space for innovation through various modular toolkits enabled by digital-age technologies. This study explores and outlines how these users simplify this wide solution space to innovate and make tangible products. Following a modularity theory perspective, it draws on case studies of users and their innovations: (1) Users with initial prototype product designs based on the Internet of things (IoT) from a maker event and (2) users with established product designs from the online community platform Thingiverse. The studies found that users reused the design in the form of existing off-the-shelf products and utilized digital fabrication and low-cost electronics hardware as a ‘glue’ to create physical and informational interfaces wherever needed, enabling bottom-up modularity. They iteratively refined their innovations, gradually replacing re-used designs with own integrated designs, reducing modularity, and reducing wastage. The study contributes to open innovation and modularity with implications on the design of products and toolkits enabled by the digital age.
CRIS-Team Scopus Importer:2020-07-31